Linear Relations of Effective Nuclear Charges and ForceConstants with Electronegativities of Diatomic Hydrides - Noorizadeh, S.; Ramezani, Z. (Asian Journal of Chemistry, 2010)
It is shown that for more than forty diatomic hydrides, HX, a linear relation between the force constant and the χ/R0 > ratio is K = 321.869501 χ/R0 – 84.291988, in which χ is the Pauling electronegativity of X atom composing the hydride. Satisfactory correlation coefficient is obtained for this line (0.985843). A new empirical relation is also found between effective nuclear charge (Zeff) and electronegativity of the X atom in these molecules, i.e., ZZeff = 0.688688χ3 + 13.780372, where n is the row's number of X atom in the periodic table. It shows that as Badger's rule, ZZeff has something to do with the third power of principal quantum number (n). A good correlation is achieved (0.960157).